Institutional Studies Of Saniri Institutions In Negeri Of Hila And Mamala As Pillars Of Local Democracy In Central Maluku - Tuanaya, Wahab; Khairunissa, Atikah; Wance, Marno (International Journal of Educational Research & Social Sciences, 2022)
The selection for a negeri (village) government is a selection process through done mata rumah perintah (the leaders of clans) that have been recognized for a long time. Among the negeri government elections in Central Maluku, there is an election conflict between Hila negeri and Mamala Negeri, which until now has not been resolved and needs further research to figure out the reasons behind the conflict. The purpose of this study is to analyze in depth the institutionalization of Saniri institutions of the Hila and Mamala negeris in the process of selecting the negerigovernment. In order to achieve the described objectives this research is designed to be carried out for 2 (two) months to explore various data from various information regarding the research problem. The type of research used is qualitative research with a descriptive analysis approach. With this approach, the author is able to provide a more detailed description and explanation of the problem of the raja (headman) election conflict in Mamala and Hila negeri, Central Maluku regency.The findings of the research field were found that (1) the conflict in the election of the Raja of the Hila negeri was caused by a conflict between mata rumah perintah, namely Ollong and Lating in carrying out the candidate for the head of the Hila negeri. The occurrence of the vacuum of the raja government because until now mata rumah parentah is still submitting a lawsuit to the Ambon City Administrative Court (PTUN). Meanwhile, the election process for the raja of Mamala government did not occur because of the election conflict in which the saniri handed over the election process to the mata rumah perintah of Malawat. Mamala negeri only has one mata rumah parentah that caused a conflict in the election of the headman (raja).